Tricuspid valve endocarditis - Hussain, Syed T.; Witten, James; Shrestha, Nabin K.; Blackstone, Eugene H.; Pettersson, Gösta B. (Annals of Cardiothoracic Surgery, 2017)
Right-sided infective endocarditis (RSIE) is less common than left-sided infective endocarditis (IE), encompassing only 5–10% of cases of IE. Ninety percent of RSIE involves the tricuspid valve (TV). Given the relatively small numbers of TVIE cases operated on at most institutions, the purpose of this review is to highlight and discuss the current understanding of IE involving the TV. RSIE and TVIE are strongly associated with intravenous drug use (IVDU), although pacemaker leads, defibrillator leads and vascular access for dialysis are also major risk factors. Staphylococcus aureus is the predominant causative organism in TVIE. Most patients with TVIE are successfully treated with antibiotics, however, 5–16% of RSIE cases eventually require surgical intervention. Indications and timing for surgery are less clear than for left-sided IE; surgery is primarily considered for failed medical therapy, large vegetations and septic pulmonary embolism, and less often for TV regurgitation and heart failure. Most patients with an infected prosthetic TV will require surgery. Concomitant left-sided IE has its own surgical indications. Earlier surgical intervention may potentially prevent further destruction of leaflet tissue and increase the likelihood of TV repair. Fortunately, TV debridement and repair can be accomplished in most cases, even those with extensive valve destruction, using a variety of techniques. Valve repair is advocated over replacement, particularly in IVDUs patients who are young, non-compliant and have a higher risk of recurrent infection and reoperation with valve replacement. Excising the valve without replacing, it is not advocated; it has been reported previously, but these patients are likely to be symptomatic, particularly in cases with septic pulmonary embolism and increased pulmonary vascular resistance. Patients with concomitant left-sided involvement have worse prognosis than those with RSIE alone, due predominantly to greater likelihood of invasion and abscess formation in left-sided IE. Patients with isolated TVIE have an operative mortality between 0–15% and excellent survival.